2017
DOI: 10.3389/fimmu.2017.01346
|View full text |Cite
|
Sign up to set email alerts
|

IL-36α Regulates Tubulointerstitial Inflammation in the Mouse Kidney

Abstract: IL-36α, a member of the IL-1 family, is a crucial mediator of inflammatory responses. We previously found that IL-36α was overexpressed in injured distal tubules (DTs); however, its pathological function remains unclear. Herein, unilateral ureter obstruction (UUO) or folic acid (FA) injection was performed in mouse kidneys to assess the role of IL-36α in kidney injury. IL-36α mRNA and protein expression significantly increased in the kidneys within 24 h after UUO. IL-36α localized to dilated DTs. IL-36α expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…Like other cytokines, IL‐36α is expressed primarily in immuno‐competent cells, but is induced in renal tubular cells in patients and rodent models with AKI and CKD [9,12]. In mice, unilateral ureteral obstruction (UUO), ischemia–reperfusion injury (IRI), glomerulonephritis, and diabetic nephropathy were reported to induce expression of IL‐36α in renal tubular cells [9,13,14]. In humans, urine levels of IL‐36α were reported to increase in patients with AKI [12] and CKD [9].…”
Section: Discussionmentioning
confidence: 99%
“…Like other cytokines, IL‐36α is expressed primarily in immuno‐competent cells, but is induced in renal tubular cells in patients and rodent models with AKI and CKD [9,12]. In mice, unilateral ureteral obstruction (UUO), ischemia–reperfusion injury (IRI), glomerulonephritis, and diabetic nephropathy were reported to induce expression of IL‐36α in renal tubular cells [9,13,14]. In humans, urine levels of IL‐36α were reported to increase in patients with AKI [12] and CKD [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the beginning of this study, we first detected the mRNA levels of 10 proinflammatory ILs both in the renal tissues of Thy-1N rats (in vivo) and in the GMCs treated with sublytic C5b-9 (in vitro), and found that mRNA of IL-6, IL-23, and IL-36a was greatly increased. Given that our previous study on Thy-1N rats has revealed the mechanism of sublytic C5b-9-induced IL-6 synthesis (5) and other researchers have reported that IL-23 and IL-36a contribute to inflammatory diseases (17,22,45,46), we selected IL-23 and IL-36a to further explore the mechanism of IL-23 and IL-36a synthesis in the GMCs upon sublytic C5b-9 attack in Thy-1N rats.…”
Section: Discussionmentioning
confidence: 99%
“…2 ), 5 , 6 9 11 16 26 suggesting that the length of primary cilia reflects the status of diseases and that cilia length changes are influenced by various disease-associated factors, including inflammatory cytokines, ROS, HIFs, and regulators of the cellular cytoskeleton and cell cycle. 7 8 9 25 26 27 42 Ichii et al 24 recently reported that interleukin (IL)-1 receptor-like 2 (IL-1RL2), an IL-36α receptor protein, was expressed at the primary cilia of distal tubular epithelial cells in the contralateral kidney after unilateral ureteral obstruction (UUO), which induced the elongation of primary cilia. 8 11 24 They proposed that the elongation of primary cilia may increase the sensitivity of cells to urine flow and IL-36α.…”
Section: Implication Of Primary Cilia Length In Kidney Diseasesmentioning
confidence: 99%
“… 2 21 22 In the kidney, the primary cilium length is dynamically altered under the influence of not only physiological factors including renal flow and the cell cycle, but also pathological factors including reactive oxygen species (ROS), oxidative stress, and cytokines. 7 8 9 23 24 25 26 Recently we and others found that acute kidney injury (AKI) and chronic kidney disease (CKD) change primary cilium lengths in the kidney epithelial cells. 5 6 7 8 9 11 27 Although it is unclear whether the change in primary cilia length is caused by these diseases because of the lack of evidence using animals with regulated cilia length, accumulated data indicate that the length of the primary cilium is associated with the progression of diseases.…”
Section: Introductionmentioning
confidence: 99%